Social media, an emerging platform for relationship building: A study of engagement with nongovernment organizations in India. Issue 1 (12th September 2017) - Tripathi, Siddharth; Verma, Sanjeev
Abstract : The purpose of this study is to explore the major determinants of nongovernment organizations (NGOs) engagement and relationship building on social media in India. Netnography with a metaphoric grounded analysis is used for the data analysis to identify these determinants, and a conceptual framework is proposed to inform the strategic direction of NGOs. The findings suggest that supporters engage with NGOs largely for personal and organizational reasons. Emotions, trust, and information needs emerge as the primary personal drivers for engagement, whereas organizational accountability, performance, brand image, and transparency emerge as organizational drivers. Behavioural intention mediates the relationship between the drivers of engagement and supporter contributions. The study suggests that as the number of supporters on social media platforms is rapidly increasing, NGOs should recognize the importance of the supporter experience while designing their marketing strategies. Given the peculiarity of supporter behaviour in relationship building by NGOs, the inclusion of more supporters may improve the welfare of society.